2016
DOI: 10.3329/icpj.v5i8.28875
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Cardiovascular Disease in Developing Countries

Abstract: Cardiovascular diseases (CVDs) have increased the mortality rate both in developing as well as developed countries, however a lower trend in death rates have been seen in developed and high income countries like USA, UK, Australia, Japan and other European countries due to improved life style, better strategic implementation, control of disease both in young and adults and especially reduced smoking habits. In developing countries CVD become an alarming situation due to prevalence of disease in early age that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
(27 reference statements)
0
13
0
Order By: Relevance
“…A study performed by Triant et al (204) observed a significantly higher prevalence of hypertension (21.2 vs. 15.9%) in a cohort of HIV-infected patients compared with their seronegative counterparts. A substantial proportion of CVD-related deaths occurs in lowand medium-income countries (169), with hypertension the leading associated risk factor (38). The durations of both HIV infection and ARV treatment are independently related to the onset of hypertension even after adjusting for variables such as obesity and the metabolic syndrome (35,134).…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study performed by Triant et al (204) observed a significantly higher prevalence of hypertension (21.2 vs. 15.9%) in a cohort of HIV-infected patients compared with their seronegative counterparts. A substantial proportion of CVD-related deaths occurs in lowand medium-income countries (169), with hypertension the leading associated risk factor (38). The durations of both HIV infection and ARV treatment are independently related to the onset of hypertension even after adjusting for variables such as obesity and the metabolic syndrome (35,134).…”
Section: Vascular Dysfunctionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the leading cause of global mortality (8,174), with ϳ80% of CVD-related deaths occurring in low-and middle-income countries (38,169). Sub-Saharan Africa (SSA) is burdened not only with a relatively high CVD prevalence but also with ϳ24.7 million people living with human immunodeficiency virus (PLHIV; ϳ70% of global HIV-positive population) (100).…”
Section: Introductionmentioning
confidence: 99%
“…Mortality from cardiovascular diseases (CVDs) had increased in both developing and developed countries. 1) 2) In developing countries, CVD has become a leading cause of disease burden. 3) However, a decreasing trend in the mortality rate has been observed in developed and high-income countries, such as the United States, United Kingdom, Australia, Japan, and Republic of Korea, owing to improved lifestyle and better disease management.…”
Section: Introductionmentioning
confidence: 99%
“… 3) However, a decreasing trend in the mortality rate has been observed in developed and high-income countries, such as the United States, United Kingdom, Australia, Japan, and Republic of Korea, owing to improved lifestyle and better disease management. 1) 2) In Korea, CVDs, in particular total heart diseases, are the leading causes of death among single-organ diseases. 4) Understanding the trends in CVD related mortality is important in reducing healthcare burden and developing strategies for reducing CVD mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Annually, about 17.7 million people die from cardiovascular diseases worldwide, accounting for 31.1% of all deaths, resulting in 151 million Disability-Adjusted Life Years (DALYs) (Roth etal., 2017) . By 2030 CVD will be responsible for more than half of all deaths in Africa (Yuyun et al, 2020) .About 80% of CVD deaths take place in low and middle income countries (Rehan et al, 2016) ,CVD is becoming one of the greatest challenges that threaten the development in such countries ,adding a heavy burden on health services that are barely dealing with communicable diseases (Gupta and Yusuf , 2019).…”
mentioning
confidence: 99%